Positive effect of Ayurvedic drugs in normalization of hematological parameters in acquired aplastic anemia - Anshul; Alok Kumar Srivastava (Wolters Kluwer Medknow Publications, 2023)
In pancytopenia due to aplastic anemia (AA), bone marrow hypocellularity leads to hazardous failure of hematopoiesis. Āyurveda treatment was given to a 30-year-old male patient known case of severe acquired AA, considering it under Pāṇḍūroga (~anemia). A study was carried out to search the effectiveness of Āyurveda medications, especially Rasāyana (~immunomodulator) mentioned in the treatment of Pāṇḍū in the management of AA. The patient was administered Rasāyana drugs, such as Śilājatukalpa, Amṛītā-Satta, Punarnavā, and Maṇḍūr having hepatoprotective, anxiolytic, and antioxidant properties, and ĀrogyavardhanīVaṭī, TrikaṭūCūrṇa. Hematological investigations of the patient were carried out every 2 months for 2 and ½ years. Erythrocyte sedimentation rate, white blood cell, and red cell distribution width coefficient of variation were in the normal range after treatment. Red blood cells, HB, and platelets were found to be increased, which were not growing before treatment. Liver function test, kidney function test, serum sodium, and potassium were normal during treatment. Complete relief in symptoms was found. The present study concludes that the severity of pancytopenia due to AA can be managed effectively with Ayurvedic medications.